Enhancing the Cell Permeability and Metabolic Stability of Peptidyl Drugs by Reversible Bicyclization. Issue 6 (30th December 2016) - Qian, Ziqing; Rhodes, Curran A.; McCroskey, Lucas C.; Wen, Jin; Appiah‐Kubi, George; Wang, David J.; Guttridge, Denis C.; Pei, Dehua
Abstract: Therapeutic applications of peptides are currently limited by their proteolytic instability and impermeability to the cell membrane. A general, reversible bicyclization strategy is now reported to increase both the proteolytic stability and cell permeability of peptidyl drugs. A peptide drug is fused with a short cell‐penetrating motif and converted into a conformationally constrained bicyclic structure through the formation of a pair of disulfide bonds. The resulting bicyclic peptide has greatly enhanced proteolytic stability as well as cell‐permeability. Once inside the cell, the disulfide bonds are reduced to produce a linear, biologically active peptide. This strategy was applied to generate a cell‐permeable bicyclic peptidyl inhibitor against the NEMO‐IKK interaction. Abstract : In the loop : Peptide bicyclization by a pair of disulfide bonds increases its proteolytic stability and cell permeability. This method also allows for regeneration of the functional linear peptide once inside the cytosol of the cell. CPP=cell‐penetrating peptide.